The weakness of postcommunist civil society reassessed - FOA, ROBERTO STEFAN; EKIERT, GRZEGORZ (European journal of political research, 2017)
During the last two decades, scholars from a variety of disciplines have argued that civil society is structurally deficient in postcommunist countries. Yet why have the seemingly strong, active and mobilised civic movements of the transition period become so weak after democracy was established? And why have there been diverging political trajectories across the postcommunist space if civil society structures were universally weak? This article uses a new, broader range of data to show that civil societies in Central and Eastern European countries are not as feeble as commonly assumed. Many postcommunist countries possess vigorous public spheres and active civil society organisations strongly connected to transnational civic networks able to shape domestic policies. In a series of time‐series cross‐section models, the article shows that broader measures of civic and social institutions are able to predict the diverging transition paths among postcommunist regimes, and in particular the growing gap between democratic East Central Europe and the increasingly authoritarian post‐Soviet space.